SOME NOTES ON LITERACY, WRITING AND HEGEMONIC POSITIONING - Ismail, Fikri Sulaiman (Ar Raniry : International Journal of Islamic Studies, 2017)
This article discusses the ideological meaning of literacy and how it should be considered before we attempt to develop various writing programs. Writing as one of main forms of human communication is prone to being ill-defined. This may lead to certain injustices in our education world, especially when literacy is not defined or seen as an ideological concept. The most familiar example of this in a learning context is that we tend to view literacy as reading and writing ignoring other values and potentials that a learner brings to a classroom such as her socio-cultural background. In the face of such challenges, this article therefore presents a conceptual framework which could serve as a reminder for educators before they attempt to develop their various education programs. The author hopes that the article would help educators determine where they should stand along this imaginary continuum of ideological literacy.This article discusses the ideological meaning of literacy and how it should be considered before we attempt to develop various writing programs. Writing as one of main forms of human communication is prone to being ill-defined. This may lead to certain injustices in our education world, especially when literacy is not defined or seen as an ideological concept. The most familiar example of this in a learning context is that we tend to view literacy as reading and writing ignoring other values and potentials that a learner brings to a classroom such as her socio-cultural background. In the face of such challenges, this article therefore presents a conceptual framework which could serve as a reminder for educators before they attempt to develop their various education programs. The author hopes that the article would help educators determine where they should stand along this imaginary continuum of ideological literacy.